A Representation of migration in Latvian mass media (2015 – 2016): Deny voice to the voiceless - Rozukalne, Anda; Kruks, Sergejs; Stakle, Alnis; Skulte, Ilva (Information & Media, 2020)
The main focus of the research is the representation of migration in Latvian media. In total, 860 publications were analysed covering both Latvian and Russian speaking media content, and the following two methodological approaches were applied: the framing analysis of textual and visual content, and historical discourse analysis in order to reveal the arguments and strategies behind the justification of intolerance.The research data reveals that the framing of migration in Latvian media is left in the hands of politicians and officials. Economic strains and threat argumentation topoi dominate media discussions. The influence of migration is explained and approached from an economic perspective, and most frequently, the intolerance against migrants is interpreted as a failure attributed to the political elite – their inability to solve problems. Intolerance justification strategies were detected in 79% of the publications. This figure confirms that the authors are aware of intolerance not being a virtue nowadays, and the causes of it must be backed up and supported. Visual messages depict migrants exclusively as unidentifiable, dangerous, as a part of an anonymous crowd.
Keywords: immigration; refugee; representation; visual communication; framing; historic discourse analysis; media; Latvia